2022
DOI: 10.3390/su142113823
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Gap between University Ambitions to Teach and Deliver Climate Change Education

Abstract: This paper aims to determine why there is a gap between university ambitions to teach climate change education, even where formal commitments and institutional incentives exist to encourage action. To explore this, acknowledgement of prior conceptual work is considered. A new matrix emerges, which conceptualizes the influences of organizational values, organisational culture, personal values and positionality-identity on the integration of climate change education into the curriculum. The role and influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This suggests that the academic role of the participants does not have a connection to their instruction of climate change material. From a wider university perspective, institutions which are unclear in their organization values, as related to climate change, can create attitude gaps among faculty and staff . To overcome these issues, universities must be more explicit in their promotion of interdisciplinary approaches to research, communication among departments, and work toward facilitating collective actions around climate change education …”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the academic role of the participants does not have a connection to their instruction of climate change material. From a wider university perspective, institutions which are unclear in their organization values, as related to climate change, can create attitude gaps among faculty and staff . To overcome these issues, universities must be more explicit in their promotion of interdisciplinary approaches to research, communication among departments, and work toward facilitating collective actions around climate change education …”
Section: Resultsmentioning
confidence: 99%
“…The Times Higher Education Impact Ranking used climate action metrics to measure the climate action performance of the universities, and the latest list for 2020 indicates that the top five universities are in New Zealand, Australia, and the United States [75]. The world needs future leaders to be forward-thinking and innovative in industry, which requires them to feel confident to challenge the stereotypes on climate action and provide alternative solutions [76].…”
Section: Discussionmentioning
confidence: 99%
“…In general, corporate social responsibility is a concept where organisations assume responsibility for incorporating environmental, economic and social concerns into their operations, culture and values whilst benefitting society and the organisations (Kot and Brzezinski, 2015). Hindley (2022) and Shealy et al (2021) specifically identified the impacts of attitudes, lived experiences and feelings, as well as the challenges of integrating climate change education in higher education, partly being an attitude problem. Many scholars recognise a need to develop tools to establish and monitor Heis's sustainable development practices (Urbanski and Leal Filho, 2015;Leal Filho et al, 2019).…”
Section: Perceived Corporate Social Responsibility and Green Culturementioning
confidence: 99%